Associations of objective versus subjective social isolation with sleep disturbance, depression, and fatigue in community-dwelling older adults. (2nd September 2019) - Cho, Joshua Hyong-Jin; Olmstead, Richard; Choi, Hanbyul; Carrillo, Carmen; Seeman, Teresa E.; Irwin, Michael R.
Abstract: Objective : Older adults are at higher risk of experiencing social isolation, which has been linked to impaired physical and mental health. The link between social isolation and health might be due to objective deprivation of social network and/or subjective experience of loneliness. This community-based cross-sectional study examined whether the associations between social isolation and behavioral symptoms including sleep disturbance, depression, and fatigue are mostly explained by its subjective component. Methods: Randomly selected 2541 community-dwelling individuals in Los Angeles aged ≥60 years were telephone-interviewed regarding their objective and subjective social isolation (respectively social network size and loneliness), sleep disturbance, depression, and fatigue. Results : When objective and subjective social isolation were separately included in multivariate regression models, both were significantly associated with behavioral symptoms. However, once they were simultaneously included in the same multivariate models, while subjective social isolation remained strongly associated (adjusted beta 0.24 for sleep disturbance [P < 0.001], 0.44 for depression [P < 0.001], 0.17 for fatigue [P < 0.001]), objective social isolation was weakly or non-significantly associated (-0.04 for sleep disturbance [P = 0.03], -0.01 for depression [P = 0.48], -0.003 for fatigue [P = 0.89]). Additionally, those with objective social isolation were found to have worse symptoms mostly when they also experienced subjective social isolation. Conclusions : Older adults with objective social isolation may experience sleep disturbance, depression, and fatigue because they feel socially isolated, not just because they are deprived of social networks. Interventions that target social isolation might serve as potential treatments for improving behavioral health of older adults, especially by targeting its subjective component.